Applying partial differential equations on networks to approximate the Max-Cut and Max-K-Cut problems - Keetch, Blaine (2020)
The Max-Cut and Max-K-Cut problems are well known combinatorial optimization problems. In this thesis we produce fast approximation methods for these problems by applying methods from partial differential equations on networks.